Distinct effects of endosomal escape and inhibition of endosomal trafficking on gene delivery via electrotransfection. - Lisa D Cervia; Chun-Chi Chang; Liangli Wang; Fan Yuan (PLoS ONE)
A recent theory suggests that endocytosis is involved in uptake and intracellular transport of electrotransfected plasmid DNA (pDNA). The goal of the current study was to understand if approaches used previously to improve endocytosis of gene delivery vectors could be applied to enhancing electrotransfection efficiency (eTE). Results from the study showed that photochemically induced endosomal escape, which could increase poly-L-lysine (PLL)-mediated gene delivery, decreased eTE. The decrease could not be blocked by treatment of cells with endonuclease inhibitors (aurintricarboxylic acid and zinc ion) or antioxidants (L-glutamine and ascorbic acid). Chemical treatment of cells with an endosomal trafficking inhibitor that blocks endosome progression, bafilomycin A1, resulted in a significant decrease in eTE. However, treatment of cells with lysosomotropic agents (chloroquine and ammonium chloride) had little effects on eTE. These data suggested that endosomes played important roles in protecting and intracellular trafficking of electrotransfected pDNA.